2009
DOI: 10.1039/b907100h
|View full text |Cite
|
Sign up to set email alerts
|

Calixarene-monophosphines as supramolecular chelators

Abstract: The calix[4]arenes 5-diphenylphosphino-17-R1-11,23-diR2-25,26,27,28-tetrapropoxycalix[4]arene (1, R1 = R2 = Br; 2, R1 = Br, R2 = H; 3, R1 = R2 = p-tolyl; 4, R1 = p-tolyl, R2 = H; 5, R1 = R2 = H; 20, R1 = p-tolyl, R2 = H), all bearing a diphenylphosphino group attached to the calixarene upper rim, have been synthesised starting from 5,11,17,23-tetrabromo-25,26,27,28-tetrapropoxycalix[4]arene. Reaction of 1-5 with [RuCl2(p-cymene)]2 leads quantitatively to monophosphine complexes, [RuCl2(p-cymene)L], in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…[20,32] A similar supramolecular interaction may, in principle, also occur in transient [Pd 0 A C H T U N G T R E N N U N G (ArX)L] complexes obtained from the calixarenyl phosphanes 6-10 (Scheme 7). Although this hypothesis remains speculative, it is consistent with the observation that subtle size modifications of the lower-rim substituents do improve the catalytic outcome, probably as a result of an induced shape modification of the calixarene receptor, which may then operate as a better receptor.…”
Section: A C H T U N G T R E N N U N G [Mola C H T U N G T R E N N U mentioning
confidence: 96%
See 1 more Smart Citation
“…[20,32] A similar supramolecular interaction may, in principle, also occur in transient [Pd 0 A C H T U N G T R E N N U N G (ArX)L] complexes obtained from the calixarenyl phosphanes 6-10 (Scheme 7). Although this hypothesis remains speculative, it is consistent with the observation that subtle size modifications of the lower-rim substituents do improve the catalytic outcome, probably as a result of an induced shape modification of the calixarene receptor, which may then operate as a better receptor.…”
Section: A C H T U N G T R E N N U N G [Mola C H T U N G T R E N N U mentioning
confidence: 96%
“…A striking feature of these ligands concerns their ability to behave as supramolecular chelators towards metal-arene moieties. [19,20] …”
mentioning
confidence: 98%
“…[2,3] While ligands of this class have found numerous applications in separation science and sensing technology, [4][5][6][7][8] catalytic properties, surprisingly, have been little studied. [9,10] This is in stark contrast with podands obtained from the related calix [4]arene cavities, [11] in particular their phosphane derivatives, [11][12][13][14][15][16][17][18][19][20] which have already led to a rich transition metal chemistry. [2,21] We have recently described the synthesis of the first mono-and diphosphines built on a resorcinarene cavitand (1-3, Scheme 1) and shown that these are suitable for complexation of transition metals, altering neither the cavity shape nor its receptor properties.…”
Section: Introductionmentioning
confidence: 66%
“…The calixarene skeleton adopts atypical pinched cone conformation [1,2], with dihedral angles between opposing phenoxy rings of 109.8°and 25.3°. The two distal rings with the smaller interplanar angle have their upper part (i.e.the Catoms in para to theoxygen atoms) pushed towards the calixarene axis (d(C1-C15 = 4.08 Å).…”
Section: Discussionmentioning
confidence: 99%